2014
DOI: 10.1002/admi.201400359
|View full text |Cite
|
Sign up to set email alerts
|

Energy Offset Between Silicon Quantum Structures: Interface Impact of Embedding Dielectrics as Doping Alternative

Abstract: Ultrasmall silicon (Si) nanoelectronic devices require an energy shift of electronic states for n‐ and p‐conductivity. Nanocrystal self‐purification and out‐diffusion in field effect transistors cause doping to fail. Here, it is shown that silicon dioxide (SiO2) and silicon nitride (Si3N4) create energy offsets of electronic states in embedded Si quantum dots (QDs) in analogy to doping. Density functional theory (DFT), interface charge transfer (ICT), and experimental verifications arrive at the same size of Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 35 publications
(74 citation statements)
references
References 43 publications
3
71
0
Order By: Relevance
“…Most importantly, it was found that “trap states” within the fundamental gap, strongly localized on single O atoms at H‐terminated Si‐NCs, do not exist with full OH‐termination. This marginalization of =O or >O bond modifications for fully OH‐terminated Si‐NCs was investigated in a bigger range up to 15 Å Si‐NCs (Si 84 (OH) 64 ), confirming and detailing results of Zhou et al The breakdown of the fundamental gap was shown to exist also for full NH 2 ‐ and fluorine (F) termination, whereby the fundamental gap was controlled by these anionic functional groups terminating the NC interface, with NC size having little impact . Using empirical density‐functional tight‐binding (DF‐TB) to investigate H‐terminated Si 35 H 36 NCs (size 11 Å) with a single O atom at the NC interface showed a massively reduced bandgap in analogy to mentioned DFT works above, whereby excitonic gaps below the value for bulk Si cast some doubt on the accuracy of such data.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, it was found that “trap states” within the fundamental gap, strongly localized on single O atoms at H‐terminated Si‐NCs, do not exist with full OH‐termination. This marginalization of =O or >O bond modifications for fully OH‐terminated Si‐NCs was investigated in a bigger range up to 15 Å Si‐NCs (Si 84 (OH) 64 ), confirming and detailing results of Zhou et al The breakdown of the fundamental gap was shown to exist also for full NH 2 ‐ and fluorine (F) termination, whereby the fundamental gap was controlled by these anionic functional groups terminating the NC interface, with NC size having little impact . Using empirical density‐functional tight‐binding (DF‐TB) to investigate H‐terminated Si 35 H 36 NCs (size 11 Å) with a single O atom at the NC interface showed a massively reduced bandgap in analogy to mentioned DFT works above, whereby excitonic gaps below the value for bulk Si cast some doubt on the accuracy of such data.…”
Section: Introductionmentioning
confidence: 99%
“…As an ultimate theoretical test, we present h-DFT results of two Si-NCs, one embedded in SiO 2 and the other embedded in Si 3 N 4 , presenting the entire system under investigation within one approximant. An interface charge transfer (ICT) of electrons from the usn-Si volume to the anions of the embedding dielectric – nitrogen (N) or oxygen (O) – is at the core of the energy shift [14]. We explain the shift of usn-Si electronic states towards the vacuum level E vac when embedded in Si 3 N 4 and further below E vac when embedded in SiO 2 by the quantum chemistry of N and O with respect to Si.…”
Section: Introductionmentioning
confidence: 99%
“…Principal parameters are the number of atoms forming the zb-NC N NC (d NC ), the bonds between ) which provides a gauge to interface charge transfer. 24 We illustrate our findings on Si NCs (diamond lattice), adhering to one single color for NC atoms. This facilitates the color coding of outermost NC atoms in accord with their number of interface bonds, see figures 3 and 4.…”
Section: Introductionmentioning
confidence: 72%
“…In a similar fashion, N bnd /N NC can be useful for investigating dopant clustering in ULSI devices as function of Si nanovolume shape, size and interface orientation, using Atom Probe Tomography as a mass spectroscopic method with ultra-high spatial resolution. 33,34 The ratio N IF (d NC )/N NC (d NC ) presents a gauge for the impact of interface charge transfer 24,35 and interface dipoles [36][37][38] onto NCs. Both phenomena have a major influence on NC electronic and optical properties.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation